What Goes into a Data Center - SIGMETRICS 2009 Tutorial - Greenberg, Albert; Maltz, Dave (2009)
Slides from a tutorial given at SIGMETRICS 2009. The data centers that implement the web and cloud computing services on which society increasingly relies are data factories on a scale rarely seen before. Each of them consumes upwards of 15 megawatts of power, hosts 50 to 200 thousand servers, and handles trillions of requests a day from customers around the globe. This tutorial will provide an overview of the components and systems that go into a modern mega-data center like those used to host web search, massive email systems, and dynamically scalable cloud applications. We'll pay special attention to interplay between these systems and the costs and requirements that motivate the solutions used in data centers. Attendees will learn about how data center applications are structured, the workloads and network traffic demands they generate, and how this affects the data center's internal and external network. We will look at the data center network, both current and newly emerging designs, and identify opportunities for innovation. Closing the loop, we will examine the techniques used to manage and provision data center applications, and explore how measurement, modeling, and incentives could be used to drive data centers towards their most economically efficient operating points. Attendees will leave with an understanding of: The state of the art in data center components, costs, and systems The requirements and economics that drive data center structure The types of workloads seen in data centers, and why they arise Some key challenges to realizing the potential of cloud computing